2009
DOI: 10.1111/j.1439-037x.2008.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post‐Anthesis Drought and Waterlogging on Accumulation of High‐Molecular‐Weight Glutenin Subunits and Glutenin Macropolymers Content in Wheat Grain

Abstract: Drought and flooding during grain filling have become major constraints to wheat quality and yield. The impacts of water deficits and waterlogging during the grain filling on contents of high‐molecular‐weight glutenin subunits (HMW‐GS) and of glutenin macropolymers (GMP) in grains of the winter wheat cultivar Yumai 34 with high grain protein content (GPC) and Yangmai 9 with low GPC were studied. At maturity, GPC was higher under drought and lower under waterlogging compared to the control, while contents of GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…The increase in GMP content was found to be correlated to the increase of HMW-GS and LMW-GS under sulphur rates. This is consistent with the other findings (Jiang et al 2009). It is suggested that sulphur application improved the accumulation of HMW-GS, LMW-GS and GMP at maturity and also favoured the quality of the wheat grain, but too much of it was unfavourable under normal nitrogen condition.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The increase in GMP content was found to be correlated to the increase of HMW-GS and LMW-GS under sulphur rates. This is consistent with the other findings (Jiang et al 2009). It is suggested that sulphur application improved the accumulation of HMW-GS, LMW-GS and GMP at maturity and also favoured the quality of the wheat grain, but too much of it was unfavourable under normal nitrogen condition.…”
Section: Discussionsupporting
confidence: 94%
“…It was reported that cultivation measures, such as nitrogen, phosphorus and sulphur, significantly affect the accumulation of GMP and HMW-GS (Jiang et al 2009, Ni et al 2014. However, little was known about the influence of the sulphur fertilizer on the content of glutenin subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants that go through periods of drought suffer decreased photosynthetic activity during this period, consequently affecting the grain formation (Jiang et al, 2009). To obtain a quality grain, it is necessary that proteins accumulate in the grain.…”
Section: Wheat Production Affected By Droughtmentioning
confidence: 99%
“…Differences between the studies may be related to the impact of N on the length of the grain-filling period and water and N stress. Jiang et al (2009) reported that water stress after anthesis increased the accumulation of HMW-GS during the early grain-filling stage. Konopka et al (2007) reported that wheat grains obtained under stress conditions were less abundant in LMW-and HMW-GS.…”
Section: Effects Of N and Water Stress On Protein Characterizationmentioning
confidence: 99%